2021
DOI: 10.3233/jbr-210742
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties and nutritional composition of fruits of the wild Himalayan strawberry (Fragaria nubicola Lindle.) in different ripening stages

Abstract: BACKGROUND: Genus Fragaria (family - Rosaceae), popular edible berry fruits with delicious flavor and considerable health benefits has many wild relatives in the Himalayan region. OBJECTIVES: The objective of the study was to characterize variability in morphology, physicochemical properties, phytochemicals, and antioxidant activity in wild Himalayan Strawberry, Fragaria nubicola along the ripening stages and among the genotypes. METHOD: Morphological and physicochemical properties, thiamine, carotenes, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Method Validation of Ligand Fishing. Two noninhibitors including methyl 2-O-β-D-glucopyranosyl-4,6-dihydroxyphenylacetate (3) and 2-O-(3-methoxyl-4,5-dihydroxybenzoyl)-4-hydroxy-6-O-β-Dglucopyranosyl-phenylacetic acid (4) and two MAO-B inhibitors including safinamide (5) and curcumin (6) were selected to construct a standard mixture, and the concentration of each compound was 0.05 mg/mL. The procedure for ligand fishing was the same as described in the "Ligand Fishing of F. nubicola Extract" section.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Method Validation of Ligand Fishing. Two noninhibitors including methyl 2-O-β-D-glucopyranosyl-4,6-dihydroxyphenylacetate (3) and 2-O-(3-methoxyl-4,5-dihydroxybenzoyl)-4-hydroxy-6-O-β-Dglucopyranosyl-phenylacetic acid (4) and two MAO-B inhibitors including safinamide (5) and curcumin (6) were selected to construct a standard mixture, and the concentration of each compound was 0.05 mg/mL. The procedure for ligand fishing was the same as described in the "Ligand Fishing of F. nubicola Extract" section.…”
Section: Chemicalsmentioning
confidence: 99%
“…2,3 Its fruit is sweet and fragrant and is often picked and sold by local kids along the streets. 4 Tibetan strawberry is a healthy food for a supplement of vitamins, beneficial phenolics, and antioxidants 5,6 and is also considered to be able to reduce neurological disorders, inflammation, and diarrhea. 4,6 It is one of the major ingredients of the famous Tibetan medicine "Twenty-five Pearl Pills" for management of central nervous system disorders.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…has garnered much interest because of its various features [1]. Consumers appreciate this fruit because of the color, shape, taste, and nutritional properties of the berry [2][3][4][5][6][7][8][9]. However, the current changes in the climate, leading to extreme weather conditions, for example, drought [10], have increased the stress on the plant, leading to uncertainty in the strawberry market.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive scientific research has confirmed that strawberries contain bioactive substances with potent antioxidant properties, such as ascorbic acid, polyphenolic compounds (ellagic acid and ferulic acid), as well as various flavonoids (such as anthocyanins, catechins, and phenolic acids). These compounds have nutraceutical effects, meaning they offer beneficial and protective properties for the human body [7][8][9].…”
Section: Introductionmentioning
confidence: 99%